Multicultural Benefits and Challenges for International Students during Period of Their Study: Case Study in Malaysia - Ramli bin Basri, Baharak Talebloo (Universitas Ahmad Dahlan, 2015)
AbstractÂ Current researches on internationalization claim âstudying overseasâ as a set of potential that assist the augmentation of âglobalizationâ. This article presents the Multicultural Benefits and challenges for International Students during Period of their Study in university Putra Malaysia. Qualitative method and convenience sampling was applied. Semi-structured interview and in depth interviews were conducted on 20 postgraduate students from various fields of study. The result of study showed that the benefits and challenges faced by the international post-graduate students can classify into distinct categories. Studying overseas offers benefits and plus points in terms of Career perspective, cultural familiarity, self-development. The challenges included problems related to facilities, social environment, education system, financial problem and international office programs. The comments made by the students could be considered by the university authorities for improvement in quality of education for international students during their studies.Keywords: International post-graduate students, challenges and benefits, qualitative method.